2011
DOI: 10.1148/radiol.11101868
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion CT Assessment of Tissue Hemodynamics Following Hepatic Arterial Infusion of Increasing Doses of Angiotensin II in a Rabbit Liver Tumor Model

Abstract: Purpose:To investigate the effects of increasing doses of angiotensin II on hepatic hemodynamics in the normal rabbit liver and in hepatic VX2 tumors by using dynamic contrast materialenhanced perfusion computed tomography (CT). Materials and Methods:This study was approved by the institutional animal care and use committee. Solitary hepatic VX2 tumors were implanted into 12 rabbits. In each animal, perfusion CT of the liver was performed before (at baseline) and after hepatic arterial infusion of varying dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 27 publications
2
12
1
Order By: Relevance
“…6B). The result of the present study is different from the results reported by literatures [13, 15, 16]. …”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…6B). The result of the present study is different from the results reported by literatures [13, 15, 16]. …”
Section: Discussioncontrasting
confidence: 99%
“… The modeling diagram of changes in perfusion parameters of other organ tumors (a rabbit liver tumor, adapted from ref [16]) induced by angiotensin II administration is shown. (A) Resting condition; (B) angiotensin II administration; adapted from ref.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…through a steal effect and reduces tumour perfusion (Zlotecki et al, 1995;Sonveaux et al, 2005;Isenberg et al, 2008). Conversely, peripheral vasoconstriction induced by adrenaline or angiotensin II increases tumour flow through an inverse steal effect (Zlotecki et al, 1995, Isenberg et al, 2008, Wright et al, 2011. Given that the abnormal tumour environment is an important contributor to tumour progression and resistance to treatment, improvements in intratumour perfusion and hypoxia may promote a more normalized tumour environment thus inhibiting tumour progression.…”
Section: Figurementioning
confidence: 99%
“…As opposed to the vasculature of the healthy liver tissue, tumor vessels will not respond to infusion of vasoconstrictive drugs, leading to an increase in preferential blood flow to the tumorous liver tissue. Various vasoconstrictors, including epinephrine, noradrenaline and angiotensin-II have shown the potential to increase the hepatic T/N blood flow ratio, in both preclinical and clinical studies [19,22,23,24,25]. Angiotensin II (AT-II) is an octapeptide hormone that acts as a vasoactive agonist and induces arterial vasoconstriction [26], with the most pronounced effect in the splanchnic vasculature.…”
Section: Introductionmentioning
confidence: 99%